Impeachment da presidente Dilma Rousseff : a legitimação do processo pelo dispositivo midiático - Jesus, Gilvan Santana de (2017)
During the years of 2015 and 2016, the president of Brazil, Dilma Vana Rousseff (2011-2016), is the target of a series of protests demanding her departure from the position through the execution of an impeachment process. Based on this political conjuncture of the country, the study tries to identify the discourses that cross and constitute our corpus of analysis. For this, the work draws on the of theoretical and methodological support of the French Discourse Analysis, in order to understand how the media discursively constructed the inpeachment process in the media, after all, the mediatic conditions reproduce, become preponderant and crystallize discourses. As a theoretical framework, the work brought the contributions from authors like Louis Althusser (1985), Pêcheux (1999; 2002; 2014), Jacqueline Authier-Revuz (1990), Jacques Guilhaumou (2006), Eni P. Orlandi (2007; 2012; 2015), Silvana M. Serrani (1993), Eduardo Guimarães (2005), Maria do Rosário V. Gregolin (2003). From this bibliographic course, some categories of analysis regarding this approach are fundamental, namely: subject, interdiscourse, discursive formation, ideology and discursive memory. In the course of constructing the empirical corpus, from printed and digital journalistic publications, the method considered different forms of placement, as well as very diverse supports. Regarding the results, the analysis reached discursive formations that legitimated the impeachment process in the media: the meanings of legal rituals and democratic majority. Also, as part of the process, the work verifies that own discursive formations of inequality between genders (male and female) build the woman in an inferior condition. Thus, in the power relations that are settled discursively in this political scenario, the discourse of the "coup" is disqualified and the impeachment of Dilma Rousseff, legitimized.